ЁШ БАДИИЙ ГИМНАСТИКАЧИЛАРДА УМУМИЙ ЧИДАМЛИЛИКНИ РИВОЖЛАНТИРИШНИНГ УСЛУБИЙ ХУСУСИЯТЛАРИ - Тўйчиев, З.Ў.; Тўйчиева, Д.Т. (SCIENCE and SOCIETY, 2023)
The main issues considered in this work is the formation of motor qualities and skills of young gymnasts at the initial stage of training, due to the complication of program exercises in rhythmic gymnastics.